Novel Action Targets of Natural Product Gliotoxin in Photosynthetic Apparatus - Guo, Yanjing; Cheng, Jing; Lu, Yuping; Wang, He; Gao, Yazhi; Shi, Jiale; Yin, Cancan; Wang, Xiaoxiong; Chen, Shiguo; Strasser, Reto Jörg; Qiang, Sheng (Frontiers in Plant Science, 2020)
Gliotoxin (GT) is a fungal secondary metabolite that has attracted great interest due to its high biological activity since it was discovered by the 1930s. It exhibits a unique structure that contains a N-C=O group as the characteristics of the classical PSII inhibitor. However, GT’s phytotoxicity, herbicidal activity and primary action targets in plants remain hidden. Here, it is found that GT can cause brown or white leaf spot of various mono- and dicotyledonous plants, being regarded as a potential herbicidal agent. The multiple sites of GT action are located in two photosystems. GT decreases the rate of oxygen evolution of PSII with an I50 value of 60 µM. Chlorophyll fluorescence data from Chlamydomonas reinhardtii cells and spinach thylakoids implicate that GT affects both PSII electron transport at the acceptor side and the reduction rate of PSI end electron acceptors' pool. The major direct action target of GT is the plastoquinone QB-site of the D1 protein in PSII, where GT inserts in the QB binding niche by replacing native plastoquinone (PQ) and then interrupts electron flow beyond plastoquinone QA. This leads to severe inactivation of PSII RCs and a significant decrease of PSII overall photosynthetic activity. Based on the simulated modeling of GT docking to the D1 protein of spinach, it is proposed that GT binds to the-QB-site through two hydrogen bonds between GT and D1-Ser264 and D1-His252. A hydrogen bond is formed between the aromatic hydroxyl oxygen of GT and the residue Ser264 in the D1 protein. The 4-carbonyl group of GT provides another hydrogen bond to the residue D1-His252. So, it is concluded that GT is a novel natural PSII inhibitor. In the future, GT may have the potential for development into a bioherbicide or being utilized as a lead compound to design more new derivatives.